Employee Benefit Programs of Some Philippine Firms - Echanis, Erlinda S. (Philippine Management Review; Vol 4 (1993), 2016)
This paper presents data on the benefit programs of a sample of Philippine firms belonging to the financial services, manufacturing, utilities and other sectors.  The data have been obtained through a questionnaire survey of managerial and non-managerial respondents in these firms.  The study reveals the form of benefits considered most important in employee choice of employers as well as in the employee’s decision to stay with the firm.  The study shows some similarities and some differences in the choice of which benefits are important among respondents belonging to different levels in the organization.